Mekong the occluding river : - Ngo, The Vinh (iUniverse, 2010)
Part travelogue, part history, and part environmental treatise, "Mekong - The Occluding River" is above all else an urgent warning that factors such as pollution, ecological devastation, and the depletion of natural resources are threatening the very existence of the Mekong River. Author Ngo The Vinh combines his vivid travel notes and collection of photographs with a meticulously researched history of the environmental degradation of the Mekong River. Translated from Vietnamese, the best-selling treatise outlines the myriad threats facing the river today.